Pulmonary hypertension associated with connective tissue disease - Srinivas Rajagopala; Molly Mary Thabah (Indian Journal of Rheumatology)
Pulmonary hypertension (PH) is an important cause of morbidity and mortality in connective tissue diseases (CTDs). CTDs may cause PH due to several mechanisms; pulmonary arterial hypertension, associated interstitial lung disease, neuromuscular disease, and/or sleep disordered breathing leading to hypoxia, associated thromboembolic PH, and pulmonary venous hypertension due to left ventricular dysfunction. PH can be measured on echocardiography, but the gold standard for diagnosis is right heart catheterization. PH-specific therapy in addition to immunosuppression is the most common treatment used though data are scant. In this narrative review, we discuss the epidemiologic burden, clinical presentation, evaluation, and management of PH in CTDs.